Practical Aspects of Building a Management Control System in a Small Communites (Research Bulletins of the Faculty of Economic Sciences, 2018)
Despite the fact that management control has been operating in the public sector since 2010, there are still difficulties in constructing efficacious and effective management control systems in small municipalities. The article presents directives for the functioning of management control, which should be used in local government units. Than ilustrate the stages of implementing the management control system and guidelines that may be useful in developing procedures, including statutes of the management control. In the next part of article describe specific solutions and tools, that can improve the management control system. It’s also point out that the implementation of particular solutions should be tailored to specific character of commune. The internal audit is important for successful of the managment control system. The use of the described solutions should help to create a management control system that will positively affect the quality of municipal management.
Keywords: managment control, internal audit, managment, commune, procedures